2016
DOI: 10.1016/j.pupt.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhaled phosphodiesterase 4 inhibitor (CHF6001) reduces the allergen challenge response in asthmatic patients

Abstract: CHF6001 is an inhaled phosphodiesterase 4 (PDE4) inhibitor in development for the treatment of obstructive lung diseases. The efficacy and safety of CHF6001 were investigated in a double blind, placebo controlled, 3-way cross-over study using the allergen challenge model. Thirty-six atopic asthmatics who were not taking inhaled corticosteroids and who demonstrated a late asthmatic response (LAR) to inhaled allergen at screening were randomised to receive CHF6001 400 μg or 1200 μg or placebo administered once a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…A double-blind, placebo-controlled, crossover study showed that compared with placebo, 400 or 1,200 μg of CHF6001 significantly attenuated the late asthmatic response (LAR) and resulted in prominent reduction in sputum eosinophil counts (Singh et al, 2016 ). When topically inhaled by ferrets and rats, no-observed-adverse-effect level dose was extremely lower than those observed for other PDE4 inhibitors (Villetti et al, 2015 ).…”
Section: Pde4 Inhibitors Under Development For the Treatment Of Inflamentioning
confidence: 99%
“…A double-blind, placebo-controlled, crossover study showed that compared with placebo, 400 or 1,200 μg of CHF6001 significantly attenuated the late asthmatic response (LAR) and resulted in prominent reduction in sputum eosinophil counts (Singh et al, 2016 ). When topically inhaled by ferrets and rats, no-observed-adverse-effect level dose was extremely lower than those observed for other PDE4 inhibitors (Villetti et al, 2015 ).…”
Section: Pde4 Inhibitors Under Development For the Treatment Of Inflamentioning
confidence: 99%
“…Allergen challenges were performed on day 9. Both CHF 6001 doses significantly inhibited allergen induced late asthmatic response (Singh et al, 2016). CHF 6001 was well tolerated, with similar numbers of adverse events in each treatment period.…”
Section: Chf 6001 Chiesimentioning
confidence: 78%
“…The recent successful results with CHF 6001, suggest that the systemic biology of PDE4 is less relevant than the lung biology for clinical efficacy in inflammatory respiratory diseases. CHF 6001 is currently the only inhaled PDE4 inhibitor advancing through clinical development and already has promising results in phase II clinical trials in asthma (Singh et al, 2016) and COPD (Singh et al, 2019). The clinical data for CHF 6001 demonstrates anti-inflammatory effects while minimizing the typical PDE4 inhibitor induced systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled PDE4 inhibitors GSK256066 and CHF6001 both inhibit allergen-induced late asthmatic responses 53,54 . An inhaled dual PDE3 and PDE4 inhibitor RPL554 has bronchodilator effects and is well tolerated in patients with asthma 55 .…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 99%